Appearance normalization of histology slides. (July 2015) - Vicory, Jared; Couture, Heather D.; Thomas, Nancy E.; Borland, David; Marron, J.S.; Woosley, John; Niethammer, Marc
Abstract : Highlights: A method for normalizing the appearance of histology slides is given. The method uses prior information to stabilize stain direction estimation. The effectiveness of the method over those not using prior information is shown. The method is shown to be effective in normalizing the appearance of faded slides. Normalization is shown to improve the performance of statistical classification. Abstract: This paper presents a method for automatic color and intensity normalization of digitized histology slides stained with two different agents. In comparison to previous approaches, prior information on the stain vectors is used in the plane estimation process, resulting in improved stability of the estimates. Due to the prevalence of hematoxylin and eosin staining for histology slides, the proposed method has significant practical utility. In particular, it can be used as a first step to standardize appearance across slides and is effective at countering effects due to differing stain amounts and protocols and counteracting slide fading. The approach is validated against non-prior plane-fitting using synthetic experiments and 13 real datasets. Results of application of the method to adjustment of faded slides are given, and the effectiveness of the method in aiding statistical classification is shown.